2008
DOI: 10.1294/jes.19.31
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular Concentrations of Steroid Hormones and PGF2.ALPHA. in Relation to Follicular Development in the Mares during the Breeding Season

Abstract: The concentrations of androstenedione, estradiol-17β, progesterone and PGF2α contained in the follicular fluid produced by the follicles in collected ovaries of mares that have had estrous phase during the breeding season were measured and analyzed the relation between the growth stage of follicles and the hormone levels in the follicular fluid. An ultrasonographic diagnostic instrument was used to measure the diameter of the follicles in order to categorize the follicles into three groups the following: 8 sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…Intrafollicular E 2 concentrations in this study were similar to that obtained by Watson and Hinrichs (), Bashir et al () in all follicle categories (25 mm: 700; 30 mm: 1,500; 35 mm: 1,800, and impeding ovulation follicles: 2000 ng/ml) and Tsukada et al () in medium (1.5–3 cm) and large follicle (3–5 cm) sizes, and higher than those obtained by Ginther (), Watson et al () and Bridges, Davidson, Chamberlain, Geisert, and Spicer (). The wide variety in the categorization of the follicular diameters and as well as the phase of the cycle could be the origin of the variations between studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Intrafollicular E 2 concentrations in this study were similar to that obtained by Watson and Hinrichs (), Bashir et al () in all follicle categories (25 mm: 700; 30 mm: 1,500; 35 mm: 1,800, and impeding ovulation follicles: 2000 ng/ml) and Tsukada et al () in medium (1.5–3 cm) and large follicle (3–5 cm) sizes, and higher than those obtained by Ginther (), Watson et al () and Bridges, Davidson, Chamberlain, Geisert, and Spicer (). The wide variety in the categorization of the follicular diameters and as well as the phase of the cycle could be the origin of the variations between studies.…”
Section: Discussionsupporting
confidence: 90%
“…This increase of P 4 in FF cifrated in 20‐fold occurs during metaphase II than during previous stages of nuclear maturation and is related to oocyte maturation (Grondahl et al, ) but not to follicle maturation (Ginther, Gastal, Gastal, Siddiqui, & Beg, ). Intrafollicular P 4 concentrations in this study were similar to that obtained by Tsukada et al () and lower than that shown by Watson and Hinrichs (), who obtained values of 20.2 ng/ml in follicles of 32–34 mm, and 98.3–401.5 ng/ml in follicles at >35 mm. In addition, Ginther et al () obtained higher concentrations (1,039 ± 103; 969 ± 159; and 1,156 ± 119 ng/ml).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, although the results of the present study are in agreement with the increase in E 2 and P 4 along the follicular growth reported by Gérard et al [37], they did not take into account the presence or absence of CL. On the contrary, Tsukada et al [12] observed no differences in P 4 concentrations in FF among follicles of different sizes.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies in different species clearly demonstrated that steroid hormones are essential for oocyte maturation and fertilisation, GC proliferation and differentiation, and eventual ovulation and luteinisation [2][3][4]. In mares, intrafollicular hormones, such as oestradiol-17β (E 2 ), progesterone (P 4 ) [6,[9][10][11][12][13][14][15], androstenedione (A 4 ) [12], testosterone (T) [13][14][15][16] and prostaglandin (PGF 2α ) [9,12], were documented. These hormones are related to the metabolic activity of ovarian cells, reflecting the physiological status of the follicle [8].…”
Section: Introductionmentioning
confidence: 99%